System safety analysis of large wind turbines. (April 2016) - Jin, Xin; Ju, Wenbin; Zhang, Zhaolong; Guo, Lianxin; Yang, Xiangang
Abstract: Wind turbines are a proven source of clean energy with wind power energy harvesting technologies supplying about 3% of global electricity consumption. Consequently, the requirements and expectations of wind turbines keep increasing. However, due to the harsh operation environment of wind turbines, modern large wind turbines are subjected to different sort of failures. Thus, safety engineering is a critical issue for making wind energy competitive to conventional sources and achieving the desirable renewable targets. Researches in the safety engineering of wind turbines have gained dramatically increasing attention. Accordingly, this paper reviews the main basic research types and methods and their corresponding applications in system safety analysis, aiming to let more experts know the current research status and also provide guidance for relevant researches.